Identification and characterization of a suppressor element in the 5'-flanking region of the mouse androgen receptor gene. - Kumar, M V (1994)
Androgens play an important role in the development and maintenance of male reproductive organs through the androgen receptor (AR). In order to study the mechanism of regulation of AR at the molecular level, a 1571 bp fragment in the 5'-flanking region of the mouse androgen receptor (mAR) gene was isolated and sequenced. Transfection of 5'-deletion constructs cloned into vectors containing the chloramphenicol acetyl transferase (CAT) gene indicated the presence of a promoter in the sequence -146 to +131. These experiments also suggested the presence of a suppressor element. Further characterization indicated that the suppressor is present between -486 to -351. It is functional in the context of the natural AR promoter and the heterologous thymidine kinase promoter. Transfection of a -546/ + 131 construct in which the putative suppressor element (-421 to -448) had been deleted caused increased basal CAT activity suggesting that the suppressor is limited to this 28 bp element in the 5'-flanking region of the mouse AR gene.